Pitting and pitting inhibition of iron in sodium sulphate solutions - Keitelman, Alberto D.; Galvele, José Rodolfo (Elsevier, 1982)
Fil: Keitelman, Alberto D. Comisión Nacional de Energía Atómica; Argentina